Acid sphingomyelinase modulates anxiety-like behavior likely through toll-like receptor signaling pathway - Huiqi Yuan; Yanan Xu; Hailun Jiang; Meizhu Jiang; Luofei Zhang; Shifeng Wei; Cao Li; Zhigang Zhao (Molecular Brain)
Abstract Recent studies have shown that abnormal activity of acid sphingomyelinase (Asm) has been associated with a range of psychiatric disorders including schizophrenia and depression. However, the role of Asm in the regulation of anxiety remains unclear. In the present study, we employed Asm-knockout (Asm KO) mice to investigate the association between Asm and anxiety using behavioral tests, RNA sequencing, q-PCR, immunohistochemical staining, and other methods. The behavioral results showed that Asm KO mice exhibit enhanced anxiety-like behaviors, such as restricted activity, reduced cumulative times in the central area, diminished exploratory interest, delayed latency to feed, through behavioral tests including open field, novelty-suppressed feeding test, elevated plus maze test, ect. Transcriptional profiling combined with bioinformatics analysis revealed the upregulation of Toll-like receptor signaling pathway related gene including Tlr1/2, Ccl3, Ccl4, Ccl5 and Cd86 in Asm KO mice, which was further confirmed by the detection of activated microglia and astrocytes through iba-1 and GFAP immunohistochemical staining. Collectively, our findings uncover a role for Asm in regulating anxiety-like behavior and suggest that it may be essential for the maintenance of emotional stability, indicating its potential as a promising target for treating anxiety disorders.